2020
DOI: 10.1371/journal.pone.0227711
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of 230 patients with unresectable hepatocellular carcinoma treated with bland transarterial embolization

Abstract: Locoregional therapies for hepatocellular carcinoma (HCC) include endovascular treatments such as chemoembolization (TACE) and bland embolization (TAE). TACE is the most adopted technique, despite a lack of definitive evidence of superiority over TAE, which is less costly and better tolerated due to the absence of chemotherapy. However, few studies have reported data on TAE monotherapy for unresectable HCC. We report our results in a cohort of 230 patients with unresectable HCC treated with TAE (TAE with 40-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The usefulness of ALBI grade in predicting overall survival has been validated in patients with HCC underwent liver resection (2), radiofrequency ablation (3), and tyrosine kinase inhibitors (4,5). The prognostic impact of ALBI grade has also been reported in patients with intermediatestage HCC underwent transarterial chemoembolization (TACE) (6). In addition, Zhao et al recently demonstrated that ALBI grade was better than Child-Pugh class in terms of stratifying prognosis in patients with HCC underwent TACE (7).…”
mentioning
confidence: 99%
“…The usefulness of ALBI grade in predicting overall survival has been validated in patients with HCC underwent liver resection (2), radiofrequency ablation (3), and tyrosine kinase inhibitors (4,5). The prognostic impact of ALBI grade has also been reported in patients with intermediatestage HCC underwent transarterial chemoembolization (TACE) (6). In addition, Zhao et al recently demonstrated that ALBI grade was better than Child-Pugh class in terms of stratifying prognosis in patients with HCC underwent TACE (7).…”
mentioning
confidence: 99%
“…All TAEs were performed without the use of intra-arterial chemotherapeutic drugs. Technical variations included microparticles TAE (P-TAE), microparticles plus cyanoacrylate glue TAE (G-TAE) and Lipiodol TAE (L-TAE), as previously reported by our group [6]. All procedures were performed by two senior operators and two junior interventional radiologists with at least three years' experience in an angiographic suite (V5000 Philips Medical System, Amsterdam, The Netherlands), equipped with cone-beam CT (Siemens Artis-Zee, Munich, Germany).…”
Section: Plos Onementioning
confidence: 99%
“…Particularly, its prognostic value has been analyzed in patients with HCC undergoing surgical resection, TACE therapy, Sorafenib therapy, or transplantation. In our Institution, however, TAE is preferred over TACE in patients with unresectable HCC as it provides similar survival rates without the side effects related to arterial chemotherapy [6,18]. Briefly, the aim of TAE therapy, as opposed to TACE, is to deploy the embolizing agent from a distal stance, in close proximity to the tumor, to achieve the maximum ischemic effect and promote necrosis of tumoral cells.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a superselective approach and careful observation of pulmonary shunting is recommended in the use of small-sized particles. In a report by Lanza et al [49], 40-or 100-µm Embozene (Varian, Austin, TX, USA) could be safely used in the superselective bland embolization procedure.…”
Section: Therapeutic Effects Of Bland Embolization With Particlesmentioning
confidence: 99%